Recurrent frothy bloat in goats associated with consumption of Strombocarpa ferox (Fabaceae) pods - Avellaneda Cáceres, Agustín; Colque Caro, Luis Adrián; Medina, Diego M.; Martinez, Olga Gladys; Echazu, Fernando; Micheloud, Juan Francisco (Ediciones INTA, 2024)
Frothy bloat is the over-distention of the rumen and reticulum, resulting from the accumulation of stable foam formed by tiny gas bubbles produced by fermentation. Normally, this functional digestive disorder occurs in ruminants when their diet consists predominantly of legumes in their vegetative state; this produces substances that reduce the surface tension, contributing to the stabilization of bubbles. This paper describes one outbreak of recurrent frothy bloat in goats in northwestern Argentina. The main clinical signs observed in affected goats were moderate to severe distension of the abdomen, agitation, and mouths half-opened, expelling a greenish foam that oozed through the corners of their lips. A gross evaluation of the necropsied animal revealed that the rumen showed a creamy homogeneous ruminal content of greenish color. The microhistological analysis of the ruminal content showed seed coats of Strombocarpa spp. The epidemiological data, clinical signs, gross findings, and microhistological analysis of the ruminal content confirmed the diagnosis of recurrent frothy bloat in goats associated with the consumption of Strombocarpa ferox green pods.